2018
DOI: 10.1007/s00784-018-2352-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the genotoxic effects of formocresol application in vital pulp therapy of primary teeth: a clinical study and meta-analysis

Abstract: This research helps to bring scientific evidence of the safe use of formocresol in deciduous pulpotomy treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…When pulpectomy is performed in multiple sessions, calcium hydroxide is the most widely used material as intracanal medication, 15 which is consistent with our results. Despite a study evaluating the mutagenic effect of formocresol 16 and its classification as a carcinogenic by the International Agency for Research on Cancer, we found that a considerable number of faculty members still recommend its use, which is in agreement with the data described in Bergoli et al 1 and Hincapié et al 2 A review addressing pulpectomy for primary teeth concluded that, while formocresol is effective, there are concerns regarding its toxicity. 5 As there are well-founded concerns and risks, biocompatible materials are preferred for use on primary teeth.…”
Section: Discussionsupporting
confidence: 87%
“…When pulpectomy is performed in multiple sessions, calcium hydroxide is the most widely used material as intracanal medication, 15 which is consistent with our results. Despite a study evaluating the mutagenic effect of formocresol 16 and its classification as a carcinogenic by the International Agency for Research on Cancer, we found that a considerable number of faculty members still recommend its use, which is in agreement with the data described in Bergoli et al 1 and Hincapié et al 2 A review addressing pulpectomy for primary teeth concluded that, while formocresol is effective, there are concerns regarding its toxicity. 5 As there are well-founded concerns and risks, biocompatible materials are preferred for use on primary teeth.…”
Section: Discussionsupporting
confidence: 87%